Albumin Dialysis in Artificial Liver Support Systems: Open-Loop or Closed-Loop Dialysis Mode?. Issue 3 (May 2015) - Pei, Yingying; Sun, Yize; Sun, Sijie; Gao, Dayong; Ding, Weiping
Abstract : In artificial liver support systems, the open-loop albumin dialysis mode (OLM) is usually used to remove protein-bound toxins from the blood of patients with liver failure. However, there is still interest in the closed-loop albumin dialysis mode (CLM) because this mode may enable not only the regeneration and reuse of albumin but also the miniaturization of artificial liver systems. In this article, we compared the two modes under a fixed amount of albumin in dialysate experimentally and theoretically. The results show that according to the detoxification efficiency in the 3 hour dialysis for removing albumin-bound bilirubin, CLM is better than OLM. The usage efficiency of albumin in CLM is also higher. Moreover, the advantage of CLM is more significant when the concentration of bilirubin in blood is lower. Under a given amount of albumin in dialysate, if the concentration of bilirubin in blood is high, one may further increase the performance of CLM by means of increasing the flow rate of the albumin dialysate or using the highly concentrated albumin dialysate.